Effectiveness of the "Hybrid-Midwifery" Model Based on WhatsApp Group and Home Visit on Early Detection of Pregnancy Danger Signs and Anxiety in Primigravida Mothers - Debora Paninsari; Debi Novita Siregar (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Delayed recognition of pregnancy danger signs contributes to maternal and neonatal morbidity and mortality. Conventional antenatal education is often limited by time constraints, resulting in inadequate knowledge retention and persistent anxiety, particularly among primigravida mothers. Hybrid models integrating digital education and personalized support may enhance both cognitive and psychological outcomes during pregnancy. Method: A quasi-experimental pretest–posttest control group study was conducted among 70 third-trimester primigravida mothers in Deli Serdang Regency, North Sumatra, Indonesia. Participants were recruited through purposive sampling and allocated into an intervention group (n=35) and a control group (n=35). The intervention group received a 4-week Hybrid-Midwifery program consisting of WhatsApp-based education and individualized home visits, while the control group received standard antenatal care. Knowledge of pregnancy danger signs was assessed using a validated questionnaire (Cronbach’s α=0.813), and anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using paired and independent t-tests. Result: The intervention group demonstrated significantly higher post-test knowledge scores than the control group (84.50 ± 5.20 vs. 62.10 ± 6.35; mean difference=22.40, 95% CI: 19.10–25.70; p<0.001; Cohen’s d=3.87). Anxiety levels were significantly lower in the intervention group than in the control group at post-test (11.20 ± 2.15 vs. 20.40 ± 3.10; mean difference=9.20, 95% CI: 7.85–10.55; p<0.001; Cohen’s d=3.48). Conclusion: The Hybrid-Midwifery model was associated with substantial improvements in knowledge of pregnancy danger signs and significant reductions in anxiety among primigravida mothers. This integrated digital-humanistic approach may serve as a feasible complementary strategy for strengthening antenatal care services in primary healthcare settings